Communication with the chronic patient – practical indicators - Kaczmarek, Marta (Przewodnik Lekarza/Guide for GPs, 2009)
Communication with a patient represents one of the non-specific curative factors, especially when it comes to treating patients with chronic illness. Conscious use of communication skills – both verbal and nonverbal – makes the diagnostic and treatment process considerably easier for the doctor. Full and consistent conveyance of medical information gives the patient an opportunity for better understanding of his or her illness and its boundaries. Doctors’ self-knowledge of their abilities and deficiencies in the communication process highly increases the level of medical care of patients with chronic illnesses, treating them as a partner, and not an object.